'What's Wrong with Carpets?'. Issue 2 (1st October 2019) - Crane, Jonathan
The short story 'What's Wrong with Carpets' continues in the Chekhovian tradition, exploring reality as it is while metonymically signifying the protagonist's whole life through the glimpse. Moreover, by representing a slice-of-life from modern Britain, with younger generations experiencing job and housing insecurity as a consequence of economic conditions, the story is freighted with subtle sociopolitical implication. The story, therefore, works counter to Charles E. May's contention that whilst the short story is able to render the mystery and ambiguity of human reality, it has never had a political agenda, and has never succeeded in emphasizing social content. The story is followed by a short essay on its composition.